Digital Voices - Lemerond, Saul,Rourks, Leigh Camacho (Bloomsbury Publishing Plc, 2023)
Intro – Half Title – Series Page – Title Page – Copyright Page – Dedication – Contents – Acknowledgments – Introduction – Chapter 1: Historical Context-Present: (The State of the Podcast) – Chapter 2: The Many Voices Classroom – Chapter 3: Craft and Metacognition – Chapter 4: Fiction: Multimodality and the Storytelling Podcast – Chapter 5: Poetry: From Performance to Analysis – Chapter 6: Creative Nonfiction: The Sound of Truth – Chapter 7: Teacher as Podcaster – Chapter 8: Audience and Publishing – Chapter 9: The Digital Divide and Podcasting – Afterword: Looking to the Future – Notes – Bibliography – Biographies – Index.
Description based on publisher supplied metadata and other sources
Keywords: Creative writing (Higher education); Internet in education; Podcasts; Electronic books